Moisture Sources for Wintertime Intense Precipitation Events Over the Three Snowy Subregions of the Tibetan Plateau. Issue 23 (8th December 2019) - Qiu, Tianpei; Huang, Wenyu; Wright, Jonathon S.; Lin, Yanluan; Lu, Ping; He, Xinsheng; Yang, Zifan; Dong, Wenhao; Lu, Hui; Wang, Bin
Abstract: Wintertime intense precipitation events often lead to severe snow disasters. In this study, a Lagrangian approach is employed to examine the evaporative moisture sources for wintertime intense precipitation events over the three snowy subregions of the Tibetan Plateau (TP) during 1979–2016, including the western TP (WTP), south central TP (SCTP), and southeastern TP (SETP). More than 80.0% of the moisture for intense precipitation over each subregion originates from terrestrial areas. Although prevailing westerly winds dominate above the TP and its surrounding areas during winter, half of the precipitation over the three subregions is supplied by evaporation from the south (i.e., the Indian Peninsula). Specifically, evaporation from the Indian Peninsula contributes 68.0%, 65.0%, and 45.0% of the moisture for intense precipitation over the WTP, SCTP, and SETP, respectively. The two primary oceanic moisture source regions for intense precipitation are the Arabian Sea and the Bay of Bengal, playing complementary roles in supplying moisture. The relative contributions of the Arabian Sea to intense precipitation over the WTP, SCTP, and SETP are 9.2%, 6.9%, and 1.1%, while those of the Bay of Bengal are 1.1%, 12.1%, and 8.6%. Southerly winds downstream of a cyclonic anomaly over the Indian Peninsula are crucial for the low‐level moisture transport from the south to the Himalayan foothills. Under the combined effects of orographic lifting and favorable large‐scale circulation patterns, moisture ascends further into the three subregions. Changes in the position and intensity of the cyclonic anomaly are particularly crucial to facilitating moisture contributions from the key source regions. Key Points: The Indian Peninsula plays a leading role in supplying moisture for intense precipitation over the snowy subregions of the Tibetan Plateau A cyclonic anomaly over the Indian Peninsula is crucial for northward lower‐level moisture transport to the Himalayan foothills A cyclonic anomaly embedded in the subtropical jet favors the onset of intense precipitation events over each snowy subregion